Reporting Joint-Venture Corporations. - Nielsen, Carl C. (The Accounting Review, 1965)
The article focuses on the use of joint-venture corporations which are described as corporations, the capital stocks of which are wholly owned by two or more other corporations. Although the emergence of the joint-venture corporation has been gradual and in several types of business, there is evidence of concentration in a few industries, like, the chemical, steel, and petroleum industries. The impact of joint-venture corporations on the financial positions of their parent companies is approached by first determining the types of relationship often existing between joint-venture corporations and their parents. It was found that in many cases joint-venture corporations depend on their parents for financial assistance, the parents actively manage the ventures, the products of many ventures are homogeneous with those of their parent companies, and contractual obligations often assure continuity of control by the parents. The article recommends that current accounting standards be revised to require that each parent's share of all its joint-venture corporations be combined with that parent's balance sheet.